Problematika Dalam Militer: Kewenangan Polisi Militer Terhadap Prajurit TNI Yang Melakukan Kejahatan Desersi - Candrakirana Candrakirana; Phireri Phireri; Muh. Fadli Faisal Rasyid (Faculty of Law Andi Sapada Institute of Social Sciences and Business, 2026)
This study aims to determine and analyze the factors that hinder the Military Police in conducting investigations against members of the Indonesian Army who commit the crime of desertion, and the factors that hinder the Military Police in conducting investigations against members of the Indonesian Army who commit the crime of desertion. This research uses a normative empirical research type with a legal and social approach. The data sources used are primary and secondary data. Data analysis will be conducted through observational-sensory and theoretical-rational methods, employing a reasoning model that first utilizes inductive logic and then continues with deductive logic. The results of this study are the Authority of the Military Police Against TNI Members Who Commit the Crime of Desertion Based on Law Number 31 of 1997 concerning Military Justice, namely receiving reports, conducting full investigations and inquiries, arresting, detaining, searching and confiscating, examining suspects and witnesses and compiling files and submitting them to the military auditor and Factors that Hinder the Implementation of Investigations by the Military Police The most frequent obstacles encountered in Denpom XIV/ 2 when tracking the whereabouts of perpetrators of the crime of desertion. In addition, other obstacles include; legal and procedural obstacles; technical and operational obstacles; institutional and structural obstacles; and social and psychological obstacles.